INTERNATIONAL OPEN ACCESS WEEK TO INFORMATION in the SL USARB (23-29 October 2017) (Confluenţe Bibliologice, 2023)
The article presents the activities carried out at the Scientific Library dedicated to the International Open Access Week, 2017 edition "Open to ..." OA Week in Balti included several activities, involving 20 librarians, attended by 394 of users, including 33 teachers, 30 PhD students and master students, 331 students. Librarians urged members of the academic community to open and post research results in USARB's Open Recearch Archive (ORA USARB) to increase visibility and raise the rating of Balti institution.